Modelling and Design of HF RFID Passive Transponders with Additional Energy Harvester - Piotr Jankowski-Mihułowicz; Włodzimierz Kalita; Mariusz Skoczylas; Mariusz Węglarski (International Journal of Antennas and Propagation, 2013)
The huge progress in electronics technology and RFID technique gives the opportunity to implement additional features in transponders. It should be noted that either passive or semipassive transponders are supplied with energy that is derived from the electromagnetic field generated by the read/write device and its antenna. This power source is used to conduct radio-communication process and excess energy could be used to power the extra electronic circuits, but the problem is to determine the additional power load impact on the RFID system proper operation and size of interrogation zone. The ability to power the supplementary electronic blocks applied in the HF passive transponders is discussed in detail this paper. The simulation model and test samples with a harvester that recovers energy from the electromagnetic field of read/write device and its antenna have been developed in order to conduct investigations. The harvested energy has been utilized to supply a microprocessor acquisition block for LTCC pressure sensor developed in research previously described by authors.